1998
DOI: 10.3138/cmlr.54.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Grammatical Gender in Italian as a Foreign Language

Abstract: This study investigated the sensitivity to gender cues exhibited by L2 learners of Italian. The participants were 64 students in first-and second-year Italian classes at the university level. Three tests were given to ascertain the students' ability to assign gender based on morphophonological, syntactic, and semantic cues. Results showed that the students were sensitive to cues in the wordfinal phonemes that reliably indicate gender and implicational scaling demonstrated a clear order of difficulty among thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
9
0
3
Order By: Relevance
“…Behavioral and electrophysiological evidence Numerous linguistic studies (Andersen 1984;Ayoun 2007; Bruhn de Garavito & White 2002;Carroll 1989;Delisle 1985;Franceschina 2001Franceschina 2005Gess & Herschensohn 2001;Hawkins 1998, cited in Hawkins 2001Hawkins & Franceschina 2004;Myles 1995;White, Valenzuela, Kozlowska-Macregor & Leung 2004) and a handful of psycholinguistic experiments (Holmes & Dejean de la Batie 1999;Guillelmon & Grosjean 2001;Oliphant 1998;Sabourin & Haverkort 2003;Sabourin, Stowe & de Haan 2006;Sabourin & Stowe 2008;Tockowitz & MacWhinney 2005), have examined how L2 learners represent and process grammatical gender. The majority of these studies have provided evidence that gender is represented differently in native and L2 speakers although this is qualified by various factors, reviewed in succession below.…”
Section: Experiments 1: Age Of Acquisition and Native Language Propertmentioning
confidence: 99%
“…Behavioral and electrophysiological evidence Numerous linguistic studies (Andersen 1984;Ayoun 2007; Bruhn de Garavito & White 2002;Carroll 1989;Delisle 1985;Franceschina 2001Franceschina 2005Gess & Herschensohn 2001;Hawkins 1998, cited in Hawkins 2001Hawkins & Franceschina 2004;Myles 1995;White, Valenzuela, Kozlowska-Macregor & Leung 2004) and a handful of psycholinguistic experiments (Holmes & Dejean de la Batie 1999;Guillelmon & Grosjean 2001;Oliphant 1998;Sabourin & Haverkort 2003;Sabourin, Stowe & de Haan 2006;Sabourin & Stowe 2008;Tockowitz & MacWhinney 2005), have examined how L2 learners represent and process grammatical gender. The majority of these studies have provided evidence that gender is represented differently in native and L2 speakers although this is qualified by various factors, reviewed in succession below.…”
Section: Experiments 1: Age Of Acquisition and Native Language Propertmentioning
confidence: 99%
“…When it comes to research projects that focused only on grammar learning strategies, it is fitting to start with research into the assignment of grammatical gender to nouns in first and additional languages, a line of inquiry that has been by and large ignored by second language acquisition specialists (e.g. Karmiloff-Smith 1977;Tucker, Lambert and Rigault 1977;Cain, Weber-Olsen and Smith 1987;Stevens 1984;Oliphant 1997). These studies revealed that, depending on learners' sensitivity to different types of cues, grammar strategies could fall into three categories, namely: morphological (e.g.…”
Section: Previous Research Into Grammar Learning Strategiesmentioning
confidence: 99%
“…Mastery of gender in adult L2 acquisition has been extensively investigated for both Romance and Germanic languages (e.g., Chini, 1995, 1998; Oliphant, 1998 for L2 Italian; Dewaele & Véronique, 2001; Granfeldt, 2005; Renaud, 2009 for L2 French; Franceschina, 2001, 2005; Hawkins & Franceschina, 2004; McCarthy 2008; Montrul et al, 2008; White, Valenzuela, Kozlowska & Leung, 2004 for L2 Spanish; Sabourin, Stowe & de Haan, 2006 for L2 Dutch; Matteini, 2010; Spinner & Juffs, 2008 for L2 German). In her longitudinal study on the acquisition of gender in Italian by speakers of different L1s, Chini (1995) distinguished a sequence of stages in the acquisition of gender agreement.…”
Section: Previous Research On the Acquisition Of Gendermentioning
confidence: 99%